Pengaruh Kompensasi dan Linkungan Kerja Non Fisik terhadap Kinerja Karyawan pada CV. 88 Kota Bima - Sahrul Ramadhan; Jaenab Jaenab (Jurnal Ilmiah Manajemen dan Kewirausahaan, 2023)
The purpose of this research is to determine the influence of compensation and non-physical work environment on employee performance at CV. 88 Bima City so that it can provide thought input to employees. This research is quantitative. This type of research is associative with the population used in this research, namely all employees at CV. 88 Bima City, totaling 47 people. The sample used in this research was all 47 employees. The sampling technique in this research is a saturated sample. Based on the criteria, the research instrument used is a questionnaire with a Likert scale. The analytical tool used in this research uses multiple linear regression analysis using SPSS Version 26.0. The results of this research are: 1) There is a partially significant influence between compensation on CV performance. 88 Bima City. 2) There is no partial significant influence between the non-physical work environment on CV performance. 88 Bima City. 3) There is a significant simultaneous influence between compensation and the non-physical work environment on CV performance. 88 Bima City.